2015
DOI: 10.1158/1535-7163.mct-14-1053
|View full text |Cite
|
Sign up to set email alerts
|

MAP17 (PDZKIP1) Expression Determines Sensitivity to the Proteasomal Inhibitor Bortezomib by Preventing Cytoprotective Autophagy and NFκB Activation in Breast Cancer

Abstract: MAP17 is a small nonglycosylated membrane protein that is overexpressed in a high percentage of carcinomas. High levels of MAP17 enhance the tumorigenic properties of tumor cells by increasing oxidative stress, which is dependent on Na þ -coupled cotransport. Here, we show that MAP17 is associated with proteins involved in protein degradation and that proteasome inhibition induces autophagy. To analyze whether MAP17 could also alter this process, we used the proteasome inhibitor bortezomib (Velcade, PS-341), w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…Similar data could be observed in the AA and AW cell lines, where the overexpression of MAP17 reduces NFκB activation and autophagy (Figure 6B, Supplementary Figure S4A). Moreover, we observed that MAP17 prevents the cytoprotective activation of NFκB and autophagy induced by bortezomib (Figure 6C, Supplementary Figure S4B) in sarcoma cell lines, a finding that has been reported previously for breast tumor cells [29]. Therefore, the inhibition of these protective pathways induced by MAP17 may explain the increase in sensitivity to bortezomib found in vivo .…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Similar data could be observed in the AA and AW cell lines, where the overexpression of MAP17 reduces NFκB activation and autophagy (Figure 6B, Supplementary Figure S4A). Moreover, we observed that MAP17 prevents the cytoprotective activation of NFκB and autophagy induced by bortezomib (Figure 6C, Supplementary Figure S4B) in sarcoma cell lines, a finding that has been reported previously for breast tumor cells [29]. Therefore, the inhibition of these protective pathways induced by MAP17 may explain the increase in sensitivity to bortezomib found in vivo .…”
Section: Resultssupporting
confidence: 82%
“…We have previously shown that MAP17 prevents cytoprotective NFκB activation and autophagy induced by bortezomib in breast tumor cells [29]. Therefore, we have tested whether these molecular markers correlate also in our PDX models prior to treatment (Figure 6A).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations